Early sealing regimes:The Bering Sea fur seal regime vis-à-vis Finnish–Soviet fishing and sealing agreements - Sellheim, Nikolas Peter (Polar Record, 2015)
Environmental management saw its early stages already in the early years of the 20th century. This note contrasts different regimes which emerged with regard to the management of seals and the seal hunt: the well-researched Bering Sea regime and the little known regimes between Finland and the Soviet Union. While the former shaped and already embedded principles of modern environmental law and has the seal population as its primary focus, the latter agreements do not make reference to the environmental dimension of the seal hunt, but must be read against the backdrop of the difficult border situations between the two countries.